Spivakâ€™s Strategic Essentialism Reading on Amy Tanâ€™s â€œThe Red Candleâ€ - Williany, Vania; Turuk, Didimus E. (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2019)
This paper analyzes the struggle of a Chinese-American woman in â€œThe Red Candleâ€, one of the vignettes in Amy Tanâ€™s novel The Joy Luck Club (1989). The main character namely Lindo Jong, is confined with patriarchy and tradition and is forced to marry her fiancÃ©e at her teenage. Fascinatingly, Lindo can free herself from the arranged marriage and her oppressive new family by a clever scheme. Spivakâ€™s strategic essentialism is then applied to scrutinize this particular issue. Indeed, by strategic essentialism, Lindo still upholds her value as a Chinese woman and her respect to her filial piety, also, she can obtain her own independence as a woman.Keywords: Chinese-American woman, patriarchy, tradition, strategic essentialism